Relative Education and the Advantage of a College Degree. Issue 4 (August 2018) - Horowitz, Jonathan
What is the worth of a college degree when higher education expands? The relative education hypothesis posits that when college degrees are rare, individuals with more education have less competition to enter highly-skilled occupations. When college degrees are more common, there may not be enough highly-skilled jobs to go around; some college-educated workers lose out to others and are pushed into less-skilled jobs. Using new measurements of occupation-level verbal, quantitative, and analytic skills, this study tests the changing effect of education on skill utilization across 70 years of birth cohorts from 1971 to 2010, net of all other age, period, and cohort trends. Higher-education expansion erodes the value of a college degree, and college-educated workers are at greater risk for underemployment in less cognitively demanding occupations. This raises questions about the sources of rising income inequality, skill utilization across the working life course, occupational sex segregation, and how returns to education have changed across different life domains.